2021
DOI: 10.1007/s10198-021-01338-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of breast cancer screening and prevention: a systematic review with a focus on risk-adapted strategies

Abstract: Objectives Benefit and cost effectiveness of breast cancer screening are still matters of controversy. Risk-adapted strategies are proposed to improve its benefit-harm and cost-benefit relations. Our objective was to perform a systematic review on economic breast cancer models evaluating primary and secondary prevention strategies in the European health care setting, with specific focus on model results, model characteristics, and risk-adapted strategies. Methods Literature databases were systematically search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 79 publications
0
12
1
Order By: Relevance
“…’Overall acceptors’ and women who thought ‘more is better’ appeared to be similar in age, but the latter group tended to have lower levels of educational attainment (see Table 1 ). As survey studies have demonstrated an association between lower levels of education and negative responses to reduced screening frequency for women at low-risk [ 5 , 13 ], it is possible that a lack of understanding may have influenced women’s negative attitudes towards low-risk screening options. Nevertheless, this will need to be confirmed by quantitative research with a larger and representative UK sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…’Overall acceptors’ and women who thought ‘more is better’ appeared to be similar in age, but the latter group tended to have lower levels of educational attainment (see Table 1 ). As survey studies have demonstrated an association between lower levels of education and negative responses to reduced screening frequency for women at low-risk [ 5 , 13 ], it is possible that a lack of understanding may have influenced women’s negative attitudes towards low-risk screening options. Nevertheless, this will need to be confirmed by quantitative research with a larger and representative UK sample.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to an increased interest in risk-stratified breast screening (RSBS), i.e., adapting screening recommendations to a woman’s breast cancer risk [ 4 ]. Simulation models suggest this approach has the potential to increase the benefits of screening (via early detection of cancer) while decreasing screening-related harms, e.g., false positive results and overdiagnosis [ 5 , 6 , 7 , 8 ]. However, the incorporation of RSBS within an existent screening programme will require major shifts in the way that screening is delivered and necessitate the involvement and agreement of all relevant stakeholders [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Personalized breast cancer screening is characterized by risk-based recommendations for the ages of screening initiation and cessation, the screening frequency, the type of screening exam, consideration of preventive treatments for high-risk women, or even decisions regarding the non-screening of low-risk women. In modeling studies, personalized risk-based approaches to the early detection of breast cancer appear to be more efficient and have a better balance of benefits and harms than age-only strategies [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although personalized screening will probably be the standard for early detection in the near future, the systematic reviews warn of the need for additional studies that assess risk estimation, acceptability, feasibility, and the legal and ethical aspects of personalized screening strategies [ 3 , 4 , 5 ]. To respond to these needs, several initiatives are underway.…”
Section: Introductionmentioning
confidence: 99%
“…The development and implementation of risk-based breast cancer control and prevention strategies can have great potential benefits and important public health implications. Moreover, risk-based breast cancer control and prevention strategy is more effective and efficient than conventional screening based on model evaluation [4,5]. A prerequisite for the implementation of personalized risk-adapted screening intervals is accurate breast cancer risk assessment [6].…”
Section: Introductionmentioning
confidence: 99%